Book Review: Communication Strategy–Strategic Public Relations for Archaeological Open-Air Museums by M.A. Zielinska and R.P. Paardekooper - Rikke Olafson (EXARC, 2014)
How a museum communicates to its audience has changed significantly in the past decades. With the introduction of the Internet and the creation of social media sites such as Facebook, Twitter and Instagram, social media has become an integrated part of the everyday life of the majority of museum visitors. Furthermore, the way in which museums understand their visitors has changed considerably also, as museums now for example talk of users instead of audiences.